THEORETICAL FOUNDATIONS AND METHODOLOGY OF LINGUISTICS IN THE FIELD OF ECONOMICS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The economic theory of language policy interprets language as an economic phenomenon, the language situation as a market relation, and language policy as an integral element of economic policy. In this article, theoretical and methodological approaches at the intersection of economics and sociolinguistics, empirical research methods, and the socio‑economic consequences of language policy are analyzed in detail.